Multireversible Redox Processes in a Self‐Assembled Nickel Pentanuclear Bis(Triple‐stranded Helicate): Structural and Spectroscopic Characterizations in the NiII5 and NiINiII4 Redox States. Issue 15 (5th August 2021) - Gouré, Eric; Gerey, Bertrand; Pécaut, Jacques; Thomas, Fabrice; Fortage, Jérôme; Collomb, Marie‐Noëlle
Abstract: We previously reported the multireversible redox behavior of bis(triple‐helicate) pentanuclear complexes of the type [{M( μ ‐bpp)3 }2 M( μ 3 ‐X)] n+ (M=Mn, Fe with X=O and Co with X=OH) with rigid tetradentate binucleating 3, 5‐bis(pyridine‐2‐yl)pyrazole (bpp − ) ligand. In this article, we focus on the nickel derivative of this family, [{Ni II ( μ ‐bpp)3 }2 Ni II 3 ( μ ‐OH)] 3+ (1 3+ ), which exhibits up to five reversible or quasi‐reversible one‐electron waves in CH3 CN solution. The two one‐electron oxidized species as well as the one‐electron reduced species with respective compositions of 4Ni II 1Ni III (1 4+ ), 3Ni II 2Ni III (1 5+ ) and 1Ni I 4Ni II (1 2+ ), were quantitatively generated by bulk electrolyses and spectroscopically characterized highlighting the high stability of this family of complexes in several redox states. In addition to the initial complex 1 3+, the mixed‐valence 1 2+ was also successfully characterized by single‐crystal X‐ray diffraction, allowing to locate the sites of successive reversible one‐electron events. 1 2+ is an unusual example of a multinuclear complex including the low‐valent Ni(I) state. Abstract : Low valency multinuclear nickel complex : A pentanuclear complex in which two axial Ni(II) units are connected to a central hydroxo‐centered Ni(II)3 trinuclear core through six bridging tetradentate bis‐pyridine‐pyrazole rigid ligand, can be stabilized in a number of unusual mixed‐valence states ranging from 1Ni(I)4Ni(II) to 3Ni(II)2Ni(III) without structural change. This work highlights the unusual electrochemical behavior of such family of electronically coupled multinuclear complexes.